A new fairy shrimp Phallocryptus tserensodnomi (Branchiopoda: Anostraca) from Mongolia - Alonso, Miguel; Ventura, Marc (Zootaxa, 2013)
A new species of Phallocryptus Biraben 1951 (Branchiopoda, Anostraca) from Mongolia is described. Phallocryptus tse-rensodnomi sp. nov. is close to P. spinosa (Milne-Edwards 1840), but both morphological and molecular analyses (Cyto-chrome Oxidase I, COI) indicate that they represent separate species. Most relevant differential features of the new species include: (1) frontal appendage provided with small ventral conical outgrowths; (2) second antennamere evenly curved, sickle-shaped; (3) distal fleshy process on labrum evenly curved forwards and tapering; (4) short stout acute spine-like projections present at each side of basal portion of gonopods; (5) female second antennae shorter and wider than in P. spinosa, tapering. Based on morphological comparisons the new species appears to be a Mongolian endemic, although some genotypes of presumed P. spinosa from Africa are similar to the new species, suggesting P. tserensodnomi might have a wider distribution.